2022
DOI: 10.1136/bmjopen-2022-062586
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of proximal humerus fractures in children: a study protocol for a retrospective cohort study

Abstract: IntroductionProximal humerus fractures (PHFs) comprise <3% of all fractures in children and adolescents. While it is accepted that minimally displaced PHFs can be treated conservatively, the management of severely displaced PHFs remains controversial, especially in older children. This study will aim to analyse the functional and quality-of-life outcomes of children with PHFs, in order to inform their optimal management.Methods and analysisWe will conduct a retrospective cohort study to evaluate the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Of the 307 eligible participants identified, only 125 agreed to participate, such that the study was likely powered to detect only very large effect sizes in the outcomes of patients according to treatment method. In our original study protocol, a sample size of 500 participants was required to identify differences in outcomes between surgical and non‐operative patients 10 . Given the 40.7% response rate, to achieve adequate power for the study, a total of 1228 eligible participants would have needed to be identified and invited to participate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 307 eligible participants identified, only 125 agreed to participate, such that the study was likely powered to detect only very large effect sizes in the outcomes of patients according to treatment method. In our original study protocol, a sample size of 500 participants was required to identify differences in outcomes between surgical and non‐operative patients 10 . Given the 40.7% response rate, to achieve adequate power for the study, a total of 1228 eligible participants would have needed to be identified and invited to participate.…”
Section: Discussionmentioning
confidence: 99%
“…Associations of patient and clinical variables with poorer clinical outcome were investigated. 10 Directed acyclic graphs (DAGs) were constructed to visualize assumed relationships between variables and to inform variable selection for statistical modelling (Figs. S1-S3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations